Perencanaan Strategis Sistem Informasi pada Perusahaan Sayur Box Menggunakan Metode Ward dan Peppard - Nining Ariati; Ben Bella Al Ghiffary Faesha Putra (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Sayur Box Company, which is engaged in the distribution of fresh food online, faces challenges in optimizing the use of information systems to support increasingly complex business operations. This study aims to design a strategic planning of information systems (SI) using the Ward Method for clustering and the Peppard Method for SI strategies that support the sustainability and growth of the company. By analyzing the functional and non-functional needs of the information system, as well as the application of both methods, this study produces strategic recommendations for the development of more integrated and effective SI at Sayur Box. The results show the importance of the role of information systems in optimizing operational efficiency, strengthening customer service, and improving data-based strategic decisions.